Urban Planning and Development in China and Other East Asian Countries - Zhang, Guanzeng; Wang, Lan (Springer Nature Singapore : Imprint: Springer, 2019)
This book examines urban development and its role in planning in China and other Asian cities. Starting with a substantial narrative on the history, development philosophy, and urban form of ancient Asian cities, it then identifies the characteristics of urban society and different phases of development history. It then discusses urbanization patterns in China with a focus on spatial layout of the city clusters in the Yangtze River Delta since the 20th Century. Lastly, it explores institutional design and the legal system of urban planning in China and other Asian cities. As a textbook for the "Model Course in English" for international students listed by the Ministry of Education in China, it helps international researchers and students to understand urban development and planning in Asian cities. .